Experience in Brazil with the use of available schistosomicides in mass treatment compaigns - Prata, Aluizio (1976)
Mass treatment for schistosomiasis ideally refers to the universal treatment of whole populations living in endemic areas, however as non toxic drugs are not yet available for schistosomiasis, treatment should not apply to ali members of such communities as with malaria. Vianna Martins15 defines it as being a simultaneous or almost simultaneous treatment of a.large number of people representative of a population. Although the lack of single dose therapy in the past made it difficult to establish mass treatment for schistosomiasis, programmes have been carried out which could be considered as mass treatments, reaching large members of people infected by Schistosoma in a well defined population.